Migration from Procedural Programming to Aspect Oriented Paradigm - Majumdar, D. (2009 IEEE/ACM International Conference on Automated Software Engineering, 2009)
Separation of Concerns' has long been a key issue in the field of Software Engineering. While developing a large complex and scalable Software, it can be observed that certain concerns have a tendency to get interleaved with the Core-Functionalities in such a way that they become inseparable. As a result of which the coder, who is supposed to be responsible only with the Core-Functionalities, is bound to take extra burden or botheration regarding the proper and accurate handling of these scattered and crosscutting concerns called Aspects. In our work we propose to devise a complete process of migrating a procedural form source-code to an aspect oriented program. We propose to devise a methodology to separate the scattered concerns from source-code through Code-Mining cascaded with a Traceability-Framework also to be framed by us. Thereafter we propose to devise a Design-Level Aspect Oriented Model for refactoring these separated code fragments in the Aspect Oriented Paradigm. Lastly, we propose to verify and validate the complete migration process.